They have killed your prophets: Roman Catholic Church priests in Nigeria and (non)state actors - Uroko, Favour C. (Theologia Viatorum (Sorenga), 2024)
This article examines why Roman Catholic priests are targeted by kidnappers and Islamic extremists in Nigeria. Although there have been studies carried out on kidnapping in Nigeria, to the best of the researcher’s knowledge, the literature on why Roman Catholic Church priests are targets of kidnappers in Nigeria is difficult to find. In this study, the literature was extended to this area. Data were collected through classified documents from national and international gazettes and periodicals and analysed using documentary analysis. According to the findings, Roman Catholic priests are heavily involved in citizen education and human rights awareness in Nigeria and command media attention whenever they are attacked. Furthermore, the huge financial returns from the priests and their active participation in politics are other motivating factors for their present victim status. The recommendations are also discussed.ContributionRoman Catholic priests of Nigeria are targeted because of their active participation in politics, their efforts to strengthen Christianity in Nigeria, their role in educating citizens about their rights and privileges, and the large ransoms obtained from the relatives of these priests when they are kidnapped. These circumstances have practical implications for theology.